1997
DOI: 10.1002/clc.4960200504
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, ischemic heart disease, and the french paradox

Abstract: Summary:Many studies have shown either an inverse relation between alcohol intake and ischemic heart disease or a U-shaped curve in which the equivalent of two drinks per day of any kind of alcohol is associated with a decreased incidence of coronary disease compared with no drinks, while higher doses result in an increased risk of infarction and stroke. Although the cardioprotective effects of most alcoholic beverages are probably due to an elevation of high-density lipoprotein as well as the ability of alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…Although the cardioprotective effects of most alcoholic beverages are probably because of ethanol-induced elevation of HDLs 35,36 and lowering of platelet aggregation, 37,38 factors other than ethanol in alcohol-containing beverages may also be responsible for the protective effect of alcoholic beverages. 7,39,40 Resveratrol, a phenolic compound found primarily in the skin of grapes and relatively abundant in red wine, has been thought to be one such factor because it has been shown to have antioxidant 6 and antiplatelet 8,14 activities. However, in-depth knowledge on whether and how resveratrol provides the protective effect against heart disease is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cardioprotective effects of most alcoholic beverages are probably because of ethanol-induced elevation of HDLs 35,36 and lowering of platelet aggregation, 37,38 factors other than ethanol in alcohol-containing beverages may also be responsible for the protective effect of alcoholic beverages. 7,39,40 Resveratrol, a phenolic compound found primarily in the skin of grapes and relatively abundant in red wine, has been thought to be one such factor because it has been shown to have antioxidant 6 and antiplatelet 8,14 activities. However, in-depth knowledge on whether and how resveratrol provides the protective effect against heart disease is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Most, biochemical studies in the literature concerning alcohol have used moderate to high doses to better understand its mechanism of action. There are some reports suggesting that at a low concentration, alcohol may be beneficial by detoxification of oxidant free radicals (Constant, 1997). However, at high concentrations it can act as a pro-oxidant by various means including induction of the mixed function oxidase CYP2E1 (Wu and Cederbaum, 2005), and formation of peroxynitrite (Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among these agents, transresveratrol (RES) may contribute to the protective effect of red wine believed to underlie the French Paradox [2][3][4][5]. Whereas definitive human clinical trials would be required to confirm a role for RES in the French Paradox, many other types of studies have shown that RES exhibits potent anti-inflammatory, antioxidant, anti-proliferative, cardioprotective and chemopreventive properties [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%